The Development of International Law in the Field of Renewable Energy - Imam Mulyana (Faculty of Law, Hasanuddin University, 2016)
Energy plays a pivotal role in ensuring economic growth, social equity and live-able environment. In this regard, the non-renewable or conventional source of energy such as oil, gas and coal continue to supply the energy demand throughout the world. Nevertheless, as the awareness of the international society towards the protection and preservation of the global environment is rapidly growing, the utilization of energy resources has been gradually shifted from the non-renewable to renewable ones. Observing the international developments in the field of energy, further international legal instruments is required to be able to regulate renewable energy activities undertaken by the countries today. Although there have been a number of rules in international law, but until recently, most of these regulations is still not legally binding. Moreover, to achieve world order that uses renewable energy, international law also had to resolve some fundamental issues, namely the issue of state sovereignty and energy security.